Asperger en la niñez: un caso clínico - educativo al sur de Lima - Sanez Ramírez, Sheyla Shydalli (2017)
The study explores a clinical educational case of a 7 year old child. André, who presents Asperger, was evaluated with psychometric, projective, specific tests, clinical observation in different environments, and mentalist skills tasks; In addition, an exhaustive interview was conducted with his parents and therapist Therapy, addressing, cognitive functions, mint Finally, psychoeducation was provided to parents, with the aim of understanding the child’s condition, acquiring behavioral guidelines and parenting styles; thus allowing greater stability in their family environment. In the last consensus of the American Psychiatric Association (2013), the terminology “Asperger Syndrome” was omitted, so the Diagnostic and Statistical Manual of Mental Disorders (DSM V), classifies it as Autistic Spectrum Disorder, Level I. On the other hand , from the point of view of the Neurodiversity, they call it, Autism Spectrum Conditions, Asperger; that I share, in this study, I will refer to Asperger, as a condition of life, omitting the names of disorders, sydrome and disease.